2016
DOI: 10.7869/tg.373
|View full text |Cite
|
Sign up to set email alerts
|

Utility of clinical and complete Rockall score in Indian patients with upper gastrointestinal bleeding

Abstract: Introduction: Acute upper gastrointestinal bleeding (AUGIB) is an important gastroenterological emergency. Role of Rockall score in stratification of risk of mortality and rebleeding in Indian patients is uncertain. Methods: This study was prospectively conducted on 175 consecutive patients admitted with AUGIB who were 18 years or above. The clinical Rockall score and complete scores calculated at admission and after endoscopy were analyzed for association with the outcome (rebleeding and mortality) for both v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 14 publications
7
14
0
Order By: Relevance
“…In our study variceal bleeding (47%) was most common cause of UGIB with chronic liver disease (43.33%) followed by Coronary artery disease (CAD) (6%) as the most common etiology. This was in consonance with a study from north India (45% & 13% respectively) (4) . Studies from eastern and southern India and all studies from the west report non-variceal as the most common cause with duodenal ulcer leading the list (2,5,7,13,14) .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study variceal bleeding (47%) was most common cause of UGIB with chronic liver disease (43.33%) followed by Coronary artery disease (CAD) (6%) as the most common etiology. This was in consonance with a study from north India (45% & 13% respectively) (4) . Studies from eastern and southern India and all studies from the west report non-variceal as the most common cause with duodenal ulcer leading the list (2,5,7,13,14) .…”
Section: Discussionsupporting
confidence: 92%
“…Rockall and PNED. Rockall score is the most validated one (4,17) . For need of treatment GBS is validated better than Rockall (15,18) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the scoring systems predict outcomes better for non-variceal UGIB. These findings are similar to an earlier published study from India [16]. Rout et al found that AIMS65 was the best predictor of mortality, probably because it does include albumin levels and INR, both measures of liver failure.…”
supporting
confidence: 91%